2003
DOI: 10.1161/01.str.0000089015.51603.cc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Infections as Risk Factors for Ischemic Stroke

Abstract: Background-Inflammatory processes have fundamental roles in stroke in both the etiology of ischemic cerebrovascular disease and the pathophysiology of cerebral ischemia. We summarize clinical data on infection and inflammation as risk or trigger factors for human stroke and investigate current evidence for the hypothesis of a functional interrelation between traditional risk factors, genetic predisposition, and infection/inflammation in stroke pathogenesis. Summary of Review-Several traditional vascular risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
314
2
23

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 462 publications
(345 citation statements)
references
References 278 publications
(228 reference statements)
6
314
2
23
Order By: Relevance
“…Several studies have reported prominent changes in proinflammatory cytokines following stroke. [20][21][22] The proinflammatory cytokines interleukin (IL)-1, tumor necrosis factor a (TNF-a), IL-6 and IL-8 have all been shown to be involved in the initiation or amplification of the inflammatory response in patients following acute cerebral ischemia. Interestingly for our purposes, some studies on experimental models have suggested that inflammatory mediators, such as the cytokine IL-1, might contribute to the extent of cerebral ischemia through their effects on specific limbic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported prominent changes in proinflammatory cytokines following stroke. [20][21][22] The proinflammatory cytokines interleukin (IL)-1, tumor necrosis factor a (TNF-a), IL-6 and IL-8 have all been shown to be involved in the initiation or amplification of the inflammatory response in patients following acute cerebral ischemia. Interestingly for our purposes, some studies on experimental models have suggested that inflammatory mediators, such as the cytokine IL-1, might contribute to the extent of cerebral ischemia through their effects on specific limbic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, an association between WBC count and IQ has not been described previously, although increased WBC count at baseline was associated with increased risk of early death in a large cohort study of SCA. 17 WBC count may serve as a marker of inflammatory mediators, which have been associated with increased risk of stroke and cognitive impairment in adults, 18 or of decreased splenic function and severe disease in SCA. 1 …”
Section: Resultsmentioning
confidence: 99%
“…[1] Recent studies have showed that S100A8 has been implicated in the pathobiology of inflammatory disorders, such as asthma, rheumatoid arthritis, and inflammatory bowel disease. [2] It is well known that the inflammatory and immune reactions are involved in cerebral ischemia reperfusion (I/R),[3,4] but whether S100A8 mediates the injury in the process of cerebral I/R is still unknown. We here report our findings concerning the expression changes and the role of S100A8 in cerebral I/R.…”
Section: Introductionmentioning
confidence: 99%